2015
DOI: 10.1097/mou.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Kidney-sparing surgery for upper tract urothelial cancer

Abstract: KSS should be regarded as a valid alternative to RNU in case of technically resectable low-risk upper tract urothelial cell carcinoma, even in case of a normal contralateral kidney. Advances in technology and biological and clinical risk estimation will make the management of UTUC more evidence based thereby lowering overtreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…With the development of conservative endoscopic treatment and the implementation of neoadjuvant chemotherapy for patients with UTUC, ureteroscopic (URS) biopsy has gained importance in the diagnosis, follow-up, and treatment decision-making. URS biopsy has been described as the most accurate predictor of the pathological stage and grade of surgical specimens 11,12 . The European Association of Urology (EAU) UTUC guidelines recommend the consideration of URS biopsy when additional information is likely to affect treatment decisions 1 .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of conservative endoscopic treatment and the implementation of neoadjuvant chemotherapy for patients with UTUC, ureteroscopic (URS) biopsy has gained importance in the diagnosis, follow-up, and treatment decision-making. URS biopsy has been described as the most accurate predictor of the pathological stage and grade of surgical specimens 11,12 . The European Association of Urology (EAU) UTUC guidelines recommend the consideration of URS biopsy when additional information is likely to affect treatment decisions 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the observed hazard can also be attributed to variations in techniques, energy application during the endoscopic surgery, laparoscopic technique, bladder cuff excision, and positive surgical margins in RNU. In a comprehensive review conducted by Lucca et al, bladder recurrence was found to be independently influenced by both patient-related and tumor-related factors [ 38 ]. Notably, the rates of bladder recurrence were similar in the endoscopic-conservative approach group compared to the RNU group.…”
Section: Discussionmentioning
confidence: 99%
“…KSS is usually restricted to patients with imperative indications such as renal insufficiency, solitary kidney, or bilateral UTUC and patients who are medically unfit for RNU. 3,14 However, the favorable outcomes achieved with segmental ureterectomy and endoscopic extirpation or fulguration ablation of the tumor have encouraged several authors to propose the use of these procedures in patients with UTUC who also have normal, functioning contralateral kidneys. The elective indications for use of KSS in a wider range of patients with UTUC have been defined in recent journals and warrants special attention.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%